Effect of new synthesized piperazine derivative [1] containing 1, 2, 4 -triazole ring on the growth of some pathogenic microorganisms - Al-Samaraie W. Khulood; Al-Rahbi S. Omar; Al-Nasiri A. Nazar (College of Pharmacy / Mustansiriyah University, 2005)
This work describes the antimicrobial activity of newly synthesized 4-methyl (3-mercapto -4- phenyl -4H- 1,2,4-Triazole -5-yl) methyl piperazine. [1]. The newly synthesized piperazine derivative was obtained from basic cyclization of the intermediate product obtained from the reaction between acetic hydrizide -4-methyl piperazine and phenylisothiosyanate(1) . [1] The in vitro tests showed antimicrobial activity against two pathogenic bacteria viz; Staphylococcus aureus (gram positive) and Escherichia coli (gram negative), in addition to the dermatophyte pathogenic fungi Trichophyton rubrum. The screening antibacterial results illustrated below indicate that concentration [50mg/ml] showed the highest inhibitory effect against Escherichia coli, while the same concentration has a moderate activity against Staphylococcus aureus. While the highest inhibitory effect against Trichophyton rubrum was achieved using the concentration [25 mg/ml].